Human Resource Performance at RSUD Kayen-Pati: The Role of Work-life Balance, Training, and Job Satisfaction - Mellyani Fadilah; Farikha Amilahaq (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the influence of work-life balance, training, and job satisfaction on employee performance at RSUD Kayen. The goal is to provide input for improving employee performance through these three key factors. Methodology: This study employed a quantitative approach. From a population of 331 employees, a probability sampling method using simple random sampling was applied, resulting in 200 respondents. Data were collected through a questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) version 4. Results: The findings show that work-life balance, training, and job satisfaction all have a positive and significant impact on employee performance. A good work-life balance directly contributes to better performance, while appropriate training and strong job satisfaction also improve work outcomes. Conclusions: This study shows that work-life balance, training, and job satisfaction have a positive impact on employee performance at RSUD Kayen. When combined, these factors improve performance, highlighting the need for a cohesive human resource strategy. Limitations: This study is limited by the fact that it did not include other influential variables such as leadership style, communication, and development. Data were obtained through a subjective questionnaire, meaning differences in perception among respondents could influence the results. Contribution: This research can be used as a reference for RSUD Kayen in formulating policies to improve employee performance through positive work-life balance, appropriate training, and increased job satisfaction.